Malaysian Primary Teachers’ Perceptions on Dyscalculia - May, Yoong Soo; Hoe, Fu Sai; Lun, Wong Wei; Shen, Lijuan (South Asian Journal of Social Sciences and Humanities, 2021)
This study aims to examine the perceptions of primary school teachers in Malaysia regarding  dyscalculia using a survey. The researchers conducted the study using a quantitative design. The  survey data had been collected using a questionnaire. The survey data were analysed using  descriptive and inferential statistics. The questionnaire was adapted from Chinn's (2020) checklist  for dyscalculia with permission from Professor Dr. Steve Chinn. Thirty Mathematics teachers from Year One to Year Three in primary schools were randomly chosen. The severity of dyscalculia  were analysed by using means and standard deviations. In contrast, independent t-tests were used  to compare the severity of dyscalculia between school locations, and analysis of variance  (ANOVA) was used to compare the severity of dyscalculia between different school types.  According to teachers' perceptions, the difficulty level for dyscalculic pupils in our country is  medium-high (M=3.684, σ=.994). There is no significant difference in dyscalculia severity  between school locations (p=.243, p>.05). However, there is a significant difference in dyscalculia  severity between school types (p=.007, p.05). Dyscalculic pupils need to be detected since primary  schools. The future agenda for this study is to design and develop an instrument in order to detect  the dyscalculic pupils among the population. The disparities in dyscalculia severity levels between  school types and s are important for the Ministry of Education, educators, teachers, and  researchers. This is because it will be useful to determine the allocations of funding and resources  so that the learning capability for pupils with different learning abilities can be improved to the  maximum.
Keywords: Dyscalculia; Dyscalculic Pupils; Mathematics; Learning Difficulty; Primary School; Survey; Quantitative